Contrasting geochemical signatures on land from the Middle and Late Permian extinction events. Issue 6 (28th April 2014) - Sheldon, Nathan D.; Chakrabarti, Ramananda; Retallack, Gregory J.; Smith, Roger M. H.
Abstract: The end of the Palaeozoic is marked by two mass‐extinction events during the Middle Permian (Capitanian) and the Late Permian (Changhsingian). Given similarities between the two events in geochemical signatures, such as large magnitude negative δ 13 C anomalies, sedimentological signatures such as claystone breccias, and the approximate contemporaneous emplacement of large igneous provinces, many authors have sought a common causal mechanism. Here, a new high‐resolution continental record of the Capitanian event from Portal Mountain, Antarctica, is compared with previously published Changhsingian records of geochemical signatures of weathering intensity and palaeoclimatic change. Geochemical means of discriminating sedimentary provenance (Ti/Al, U/Th and La/Ce ratios) all indicate a common provenance for the Portal Mountain sediments and associated palaeosols, so changes spanning the Capitanian extinction represent changes in weathering intensity rather than sediment source. Proxies for weathering intensity chemical index of alteration, ∆ W and rare earth element accumulation all decline across the Capitanian extinction event at Portal Mountain, which is in contrast to the increased weathering recorded globally at the Late Permian extinction. Furthermore, palaeoclimatic proxies are consistent with unchanging or cooler climatic conditions throughout the Capitanian event, which contrasts with Changhsingian records that all indicate a significant syn‐extinction and post‐extinction series of greenhouse warming events. Although both the Capitanian and Changhsingian event records indicate significant redox shifts, palaeosol geochemistry of the Changhsingian event indicates more reducing conditions, whereas the new Capitanian record of reduced trace metal abundances (Cr, Cu, Ni and Ce) indicates more oxidizing conditions. Taken together, the differences in weathering intensity, redox and the lack of evidence for significant climatic change in the new record suggest that the Capitanian mass extinction was not triggered by dyke injection of coal‐beds, as in the Changhsingian extinction, and may instead have been triggered directly by the Emeishan large igneous province or by the interaction of Emeishan basalts with platform carbonates.